Design and Performance of a 16S rRNA-Targeted Oligonucleotide Probe for Detection of Members of the Genus Bdellovibrio by Fluorescence In Situ Hybridization - Mahmoud, Khaled K. (American Society for Microbiology (ASM), 2007)
A 16S rRNA-targeted, Cy3-labeled oligonucleotide probe was designed to detect members of the genus Bdellovibrio by fluorescence in situ hybridization. Specific hybridization conditions were established; however, the detection of bdellovibrios in environmental samples required enrichment, confirming that Bdellovibrio spp. are not present in large numbers in the environment.